Online and Hybrid Teaching Effects on Graduate Attributes: Opportunity or Cause for Concern? - Kelum A. A. Gamage; Kerlin Jeyachandran; Shyama C. P. Dehideniya; Chris G. Lambert; Allan E. W. Rennie (MDPI AG, 2023)
The opportunity to develop graduate attributes beyond disciplinary expertise is an essential component of any degree programme, and students should develop these during their time within higher education. Graduate attributes can be considered as high-level skills and qualities beyond technical knowledge, which enable higher education institutions to produce more employable graduates. However, there are significant challenges in developing such skills and qualities, where remote teaching and learning complicate this further. Online teaching does not wholly derail the opportunities for students to achieve existing graduate attributes-in contrast, it also creates opportunities for innovation and shapes graduates in preparation to be the next-generation workforce. In this paper, we aim to study and synthesise existing knowledge on the effect of online hybrid teaching on graduate attributes. A systematic literature survey was completed revealing that educational institutions continue using online or hybrid instructional modes, affecting graduate attributes positively and negatively. Therefore, to effectively develop graduate attributes, there is a requirement for fundamental changes in instructional strategies, teaching-learning behaviours, upgrading of facilities and curriculum adaptations. We review graduate attributes in the higher education literature, including the impacts resulting from remote teaching and learning. The paper also identifies the general challenges to developing graduate attributes, as well as more specific challenges as a result of hybrid and online teaching and learning.